FedCLAR: Federated Clustering for Personalized Sensor-Based Human Activity Recognition - Presotto, Riccardo; Civitarese, Gabriele; Bettini, Claudio (Proceedings of the IEEE International Conference on Pervasive Computing and Communications, 2022)
Sensor-based Human Activity Recognition (HAR) has been a hot topic in pervasive computing for several years mainly due to its applications in healthcare and well-being. Centralized supervised approaches reach very high recognition rates, but they incur privacy and scalability issues. Federated Learning (FL) has been recently proposed to mitigate these issues. Each subject only shares the weights of a personal model trained locally, instead of sharing data. A cloud server is in charge of aggregating the weights to generate a global model. However, since activity data is non-independently and identically distributed (non-IID), a single model may not be sufficiently accurate for a large number of diverse users. In this work, we propose FedCLAR, a novel federated clustering method for HAR. Based on the similarity of the local model updates, the cloud server in FedCLAR derives groups of users that exhibit similar ways of performing activities. For each group, FedCLAR uses a specialized global model to mitigate the non-IID problem. We evaluated FedCLAR on two well-known public datasets, showing that it outperforms state-of-the-art FL solutions.